3x+9=15forx

Simple and best practice solution for 3x+9=15forx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9=15forx equation:


Simplifying
3x + 9 = 15forx

Reorder the terms:
9 + 3x = 15forx

Solving
9 + 3x = 15forx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15forx' to each side of the equation.
9 + -15forx + 3x = 15forx + -15forx

Combine like terms: 15forx + -15forx = 0
9 + -15forx + 3x = 0

Add '-9' to each side of the equation.
9 + -15forx + -9 + 3x = 0 + -9

Reorder the terms:
9 + -9 + -15forx + 3x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -15forx + 3x = 0 + -9
-15forx + 3x = 0 + -9

Combine like terms: 0 + -9 = -9
-15forx + 3x = -9

Reorder the terms:
9 + -15forx + 3x = -9 + 9

Combine like terms: -9 + 9 = 0
9 + -15forx + 3x = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(3 + -5forx + x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(3 + -5forx + x)' equal to zero and attempt to solve: Simplifying 3 + -5forx + x = 0 Solving 3 + -5forx + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -5forx + -3 + x = 0 + -3 Reorder the terms: 3 + -3 + -5forx + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5forx + x = 0 + -3 -5forx + x = 0 + -3 Combine like terms: 0 + -3 = -3 -5forx + x = -3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) | | 4/3-1 | | 2b-7b=5 | | 8x^2-13x-6x=0 | | x-ba=c+da | | a-bx=c+dx | | x+2(x+1)=122-3(x+2) | | -8(m+1)-m-12=-9(m+4)+16 | | x+(x-3)=9 | | -8=m/6-9 | | -7(2b+2)+15b-8=0 | | 2/3*2 | | 7x+5=4x+9 | | 8-x=4x+8 | | 512/252 | | 2x-11=1x+11 | | -2x^2-3x-9=0 | | 2x-2y*1=-4*1 | | 11(v+1)-3v=4(2v+4)-24 | | m/7+4=3m | | 55=6000/12(r) | | 9x-(5x+7)=6x-13 | | 3.8q-5.7-4.3q=-1.5q-211 | | 4+(-50)= |

Equations solver categories